Angiotensin-Converting Enzyme (ACE) Inhibitors and Angiotensin Receptor Blockers (ARB) Are Protective Against ICU Admission and Mortality for Patients With COVID-19 Disease - ElAbd, Rawan; AlTarrah, Dana; AlYouha, Sarah; Bastaki, Hamad; Almazeedi, Sulaiman; Al-Haddad, Mohannad; Jamal, Mohammad; AlSabah, Salman (Frontiers in Medicine, 2021)
Abstract Introduction Corona Virus disease 2019 (COVID-19) caused by the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic. The aim of this study was to investigate the impact of being on an Angiotensin-Converting Enzyme Inhibitors (ACEI) and/or Angiotensin Receptor Blockers (ARB) on hospital admission, on the following COVID-19 outcomes: disease severity, ICU admission, and mortality. Methods The charts of all patients consecutively diagnosed with COVID-19 from the 24th of February to the 16th of June of the year 2020 in Jaber Al-Ahmed Al-Sabah hospital in Kuwait were checked. All related patient information and clinical data was retrieved from the hospitals electronic medical record system. The primary outcome was COVID-19 disease severity defined as the need for Intensive Care Unit (ICU) admission. Secondary outcome was mortality Results A total of 4,019 COVID-19 patients were included, of which 325 patients (8.1%) used ACEI/ARB, users of ACEI/ARB were found to be significantly older (54.4 years vs. 40.5 years). ACEI/ARB users were found to have more co-morbidities; diabetes (45.8% vs. 14.8%) and hypertension (92.9% vs 13.0%). ACEI/ARB use was found to be significantly associated with greater risk of ICU admission in the unadjusted analysis (OR, 1.51 (95% CI: 1.04 – 2.19), p=0.028). After adjustment for age, gender, nationality, coronary artery disease, diabetes and hypertension, ICU admission was found to be inversely associated with ACEI use (OR, 0.57 (95% CI: 0.34 – 0.88), p=0.01) and inversely associated with mortality (OR, 0.56 (95% CI: 0.33 – 0.95), p=0.032). Conclusion The current evidence in the literature supports continuation of ACEI/ARB medications for patients with co-morbidities that acquire COVID-19 infection. Although, the protective effects of such medications on COVID-19 disease severity and mortality remain unclear, the findings of the present study support the use of ACEI/ARB medication.